Isolasi dan Karakterisasi Î±-Selulosa Dari Kulit Buah Matoa (Pometia pinnata) - Fauzan Aulia Akbar; Edi Nasra; Desy Kurniawati; Deski Beri; Hary Sanjaya (Departemen Kimia FMIPA UNP, 2023)
Cellulose isolation from the matoa fruit peel (Pometia pinnata) has been carried out by means of acid hydrolysis and alkaline hydrolysis. The purpose of this study was to isolate cellulose in the peel of matoa fruit and determine what is the purity level of cellulose contained in the peel of matoa fruit, FTIR is used to identify cellulose functional groups in matoa fruit peel. Results of this study, an yeild of the results of cellulose isolation of matoa peel was 41.3% with the purity level of cellulose of matoa fruit peel of 47.63%. The results of characterization using FTIR are known to have cellulose groups contained in the matoa peel such as -OH, -CH, and C-O groups which are the main functional groups in cellulose.